(untitled) - Middleton, Timothy (Hoboken, N.J., 2004)
In clear-cut language, The Bond King reveals the proven techniques of Gross's Total Return Method which has resulted in the largest actively managed fund in the United States. Filled with concept-clarifying examples, The Bond King explains: The ways a bond investor can actively manage a portfolio of fixed-income securities; Why predicting secular (long-term) domestic and global changes is key to Gross's stunning track record; How the writings of "three wise men" forged his market knowledge; Why capital preservation, aside from increasing total return, is the first and ultimate goal of bond investors; Why foreign bonds offer outstanding opportunities to Total Return investors; Why Gross regards Treasury Inflation-Protected Securities (TIPS) as the single best idea for bonds in the next five years.
Keywords: Bonds,Bond market,Investments